Analisis Kesesuaian Wilayah Pengembangan Sapi Potong di Pulau Nunukan dan Sebatik - Muh. Ridwan; Muhammad Aminawar (Faculty of Agriculture, Musamus University, 2021)
Nunukan district has resources and strategic position that should be managed efficiently. One of the few things that need to be prepared to achieve the efficiency is to plan and manage the spatial appropriately. Nunukan Regency has set the agricultural area, however it is still global, zoning of beef cattle livestock sub-sector is not markedly available. Determination of the suitability of the development region was undertaken with a study of agro-ecological condition, analysis of potential of natural resources, human resources, contributing factors, and the region designation. This study aims to provide an overview of how to analyze the suitability of region for beef cattle development, direction of development and program orientation in beef cattle development based on secondary data on the islands of Nunukan and Sebatik. The level of regional suitability was expressed relatively between districts. Determination of classes conducted by the method of scoring and weighting refers to a method of the Faculty of Animal Husbandry and directorate general of animal husbandry with modifications according to the field conditions. The result showed that Nunukan district is the highest priority for the development of beef cattle, so an acceleration for development is needed, districts of South Nunukan and Sebatik are in medium category with an orientation program in the form of training, while the other regions of Sebatik are in the low category with an orientation program in the form of beef cattle farm development.